Toward a realistic optoelectronic-based kinematic model of the hand: representing the transverse metacarpal arch reduces accessory rotations of the metacarpophalangeal joints. Issue 6 (25th April 2016) - Cocchiarella, David M.; Kociolek, Aaron M.; Tse, Calvin T.F.; Keir, Peter J.
Abstract : A kinematic model representing the versatility of the human hand is needed to evaluate biomechanical function and predict injury risk in the workplace. We improved upon an existing optoelectronic-based kinematic hand model with grouped metacarpals by defining segmented metacarpals and adding the trapeziometacarpal joint of the thumb. Eight participants performed three static postures (neutral pose, cylinder grip, cap grip) to evaluate kinematic performance of three different models, with one, two, and four metacarpal segment(s). Mean distal transverse metacarpal arch angles in the four-segment metacarpal model were between 22.0° ± 3.3° (neutral pose) and 32.1° ± 3.7° (cap grip). Representation of the metacarpals greatly influenced metacarpophalangeal joint rotations. Both the two- and four-segment metacarpal models displayed significantly lower metacarpophalangeal joint 'supination' angles (than the one-segment model) for the fourth and fifth fingers. However, the largest reductions were for the four- versus one-segment models, with mean differences ranging from 9.3° (neutral pose) to 17.0° (cap grip) for the fourth finger and 16.3° (neutral pose) to 33.0° (cylinder grip) for the fifth finger. MCP joint abduction/adduction angles of the fourth and fifth fingers also decreased with segmentation of the metacarpals, although the lowest magnitudes generally occurred in the four-segment model. Overall, the four-segment metacarpal model produced the lowest accessory rotations in non-dominant axes, and best matched previous radiological studies that found MCP joint pronation/supination angles were typically less than 10°. The four-segment metacarpal model, with improved anatomic fidelity, will better serve future studies of detailed actions of the hand in clinical or work applications.